Growth hormone releasing factor: comparison of two analogues and demonstration of hypothalamic defect in growth hormone release after radiotherapy. - Grossman, A; Lytras, N; Savage, M; Wass, J; Coy, D; Rees, L; Jones, A; Besser, G (1984)
Human pancreatic growth hormone releasing factor (hpGHRF(1-40] stimulates the release of growth hormone in normal subjects and some patients with growth hormone deficiency. A study comparing the shorter chain amidated analogue hpGHRF(1-29) with an equivalent dose of hpGHRF(1-40) in seven normal subjects showed no significant difference in growth hormone response between the two preparations. Six patients with prolactinomas were also tested; these patients had received megavoltage radiotherapy previously but had developed growth hormone deficiency as shown by insulin induced hypoglycaemia. In all six patients 200 micrograms hpGHRF(1-40) or hpGHRF(1-29)NH2 produced an increase in the serum growth hormone concentration. These data suggest that hpGHRF(1-29)NH2 may be useful for testing the readily releasable pool of growth hormone in the pituitary and that cases of hypothalamo-pituitary irradiation resulting in growth hormone deficiency may be due to failure of synthesis or delivery of endogenous GHRF from the hypothalamus to pituitary cells.